Fiscal consolidation, institutional quality, and debt-growth nexus in development countries - Ng, Chee Hung (2014)
This study examines the impact of institutional quality on fiscal consolidation and it influences on debt-growth nexus in developing countries during 1980 to 2008. There are three specific objectives, namely (i) to examine the influence of institutional quality on fiscal consolidation program, (ii) to determine the causality effect between debt ratio and economic growth, and (iii) to identify the threshold level of debt-to-GDP ratio in developing countries. Motivated by the lacks of studies regarding the role of institutions on the fiscal consolidation efforts, the first objective of this thesis aims to provide some empirical analysis on the effect of institutional quality on the progress of fiscal consolidation program, using a core sample of 71 developing countries over the period 1980 to 2008. The empirical results based on the panel generalized method of moments (GMM) indicate that better institutions tend to reduce deficit budget account in developing countries, but failed to do so in the level of debt accumulation. In other words, fiscal consolidation programs through reducing budget deficit account are more attainable with better quality of institutions. In addition, stronger institutions may allow these countries to involve in more fiscal expansionary programs and achieve higher sustainable level of debt. The second objective is motivated by the fact that the issues of debt and growth has been gaining attention most recently especially in the study by Reinhart and Rogoff (2008) on their paper entitled “Growth in a Time of Debt”. However, far too little attention has been paid to the causality relationship between debt and economic growth. This thesis seeks to find out the direction of causality between these two variables in developing countries with the inference of institutional quality using the panel causality based on system generalized method of moments (GMM) estimations. The empirical results show that there is a causality effect running from economic growth to debt. The findings also demonstrate that other causal effects are detected, running from growth and debt to institutional quality, but no direct causal effect running from institutional quality to both economic growth and debt. The last objective of the thesis, which is motivated by the inappropriate threshold estimation of debt which overlooked the study in developing countries as well as the improper use of methodology, aims to provide some empirical evidence on finding the sustainable debt threshold value for developing countries. In the literature, the debt-to-gross domestic product (GDP) threshold for developed countries is 90 per cent, whereas for developed and developing countries is 77 per cent. A dynamic panel threshold model is employed to estimate the threshold value for the debt-to-GDP ratio on a growth model. The empirical results suggest a threshold of 44 per cent of debt-to-GDP level in developing countries. This finding reveals that developing countries have a lower threshold of debt-to-GDP ratio compared to developed countries, as well as the combination of developed and developing countries in the literature. The findings also reveal that debt-to-GDP is negatively associated with economic growth especially above the threshold level.